How Implementing Space Capabilities can Realize the Directives of Hungary’s National Security Strategy - Gábor, Nagy; Singlár, Gergely; Kelemen, Zsolt; Mészáros, Dalma; Tulok, András; Kövesi, Csaba; Danyi, István; Paróczai, Sándor; Hamar, Dénes; Puszta, Lóránt (International Journal of Engineering and Management Sciences, 2021)
The Hungarian Government has released its decree on Hungary’s National Security Strategy, which provides a comprehensive picture of Hungary’s present state of security, sets out the country’s goals and directives to be achieved as well as the necessary government tools and tasks. Significant contributions can be made to the implementation of many of these directives by national space capabilities based on a Hungarian satellite system. In this study we intend to show the validity of this statement by presenting an overview of the legitimacy, features and possible benefits of national space-based capabilities as well as the necessary tasks involved in their implementation.